2020
DOI: 10.1155/2020/6940132
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological Survey on Medicinal Plants Used by Traditional Healers in Central and Kara Regions of Togo for Antitumor and Chronic Wound Healing Effects

Abstract: Cancer is an emerging public health problem in sub-Saharan Africa. Several medicinal plants are used by traditional healers to treat tumors. In Togo, there are no recorded data for these plants but traditional healers claim to cure tumors with some success. So, information on medicinal plants used to cure human tumors and cancer could be of great importance for their widespread use and scientific validation. e present ethnopharmacological survey aims to record information on antitumor plants in central and Kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Te sociodemographic characteristics of the traditional healers are presented in Table 1. Te age distribution demonstrates that elders were more involved in this practice than young people, which was also revealed in studies carried out in Togo and Ethiopia [96,97]. According to the results, women in this practice were in the minority, which confrms the fndings of Upadhya et al [8].…”
Section: Demographic Characteristics Of Surveyed Traditionalsupporting
confidence: 55%
“…Te sociodemographic characteristics of the traditional healers are presented in Table 1. Te age distribution demonstrates that elders were more involved in this practice than young people, which was also revealed in studies carried out in Togo and Ethiopia [96,97]. According to the results, women in this practice were in the minority, which confrms the fndings of Upadhya et al [8].…”
Section: Demographic Characteristics Of Surveyed Traditionalsupporting
confidence: 55%
“…Previous studies have confirmed high numbers 3 , 4 , 16 , 17 , 23 , 28 , 30 32 while other studies have shown low numbers. 25 , 33 36 …”
Section: Discussionmentioning
confidence: 99%
“…The frequent use of fenugreek and turmeric by cancer patients has also reported by some previous Moroccan studies. 4 17 Other studies have also revealed the frequency of use of garlic 22 , 23 25 as well as the use of turmeric 22 – 37 and also for thyme. 37…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants may offer new alternatives to these limited therapeutic options. erefore, it has been an increased scientific interest in the study of materials from a plant source as an anticancer compound [10,11]. Many studies in the literature have reported the expressive anticarcinogenic and antimutagenic activities of plants that contained phenolic compounds, flavonoids, and tannins due to their antioxidant properties [12][13][14].…”
Section: Introductionmentioning
confidence: 99%